Intestinal Inflammation in Chilean Infants Fed With Bovine Formula vs. Breast Milk and Its Association With Their Gut Microbiota - Ossa, Juan C.; Yáñez, Dominique; Valenzuela, Romina; Gallardo, Pablo; Lucero, Yalda; Farfán, Mauricio J. (Frontiers in Cellular and Infection Microbiology, 2018)
Introduction: Compared to bovine formula (BF), breast milk (BM) has unique properties. In the newborn intestine, there is a homeostatic balance between the counterparts of the immune system, which allows a physiological inflammation, modulated by the gut microbiota. Many studies have attempted to understand the effect of BF vs. BM, and the changes in the gut microbiota, but few also focus on intestinal inflammation. Methods: We conducted a cohort study of newborn infants during their first 3 months. In stool samples taken at 1 and 3 months (timepoints T1 and T3), we quantified calprotectin, IL-8 and α1-antitrypsin by ELISA and we evaluated the expression of IL8 and IL1β genes by RT-qPCR. To determine the microbiota composition, the 16S rRNA gene was amplified and sequenced using 454 pyrosequencing. Sequences were clustered into operational taxonomic units (OTUs). Results: In total 15 BM and 10 BF infants were enrolled. In the BM group, we found calprotectin and α1-antitrypsin levels were significantly elevated at T3 compared to T1; no differences were found between T1 and T3 in the BF group. A comparison between the BM and BF groups showed that calprotectin levels at T1 were lower in the BM than the BF group; this difference was not observed at T3. For IL-8 levels, we found no differences between groups. A gene expression analysis of the IL8 and IL1β genes showed that infants from the BF group at T1 have a significantly increased expression of these markers compared to the BM group. Gut microbiota analyses revealed that the phylum Bacteroidetes was higher in BM than BF, whereas Firmicutes were higher in BF. A redundancy analysis and ANOVA showed BM has a community structure statistically different to BF at T1 but not at T3. Compared to BF, BM at T1 showed a higher representation of Enterococcus, Streptococcus, Enterobacter, Lactococcus, and Propionibacterium. Conclusions: We found a basal state of inflammation in the infants' intestine based on inflammation markers. One month after birth, infants receiving BF exhibited higher levels of inflammation compared to BM.